Analysis of Needs for E-Modules based Problem Based Learning on Renewable Energy Materials to Improve Creative Thinking Skills of SMA Negeri 1 Namang Students - Muniatuz Azairok; Ida Sriyanti; Ketang Wiyono (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2023)
This study aims to explore the needs and interests of students in learning Physics through the use of electronic modules at SMA Negeri 1 Namang with a descriptive research approach. The research involved 99 students from three classes. The results of the preliminary study show that only 25.3% of students have knowledge of electronic modules, while their use in schools is still rare. However, all students showed a high interest in learning using electronic modules that contain images, text and videos. Electronic modules are considered as learning resources that facilitate understanding of the material and improve the overall learning process. Students expect electronic modules that are concrete, easy to understand, and able to improve creative thinking skills. They also want material that is explained in depth and relevant to everyday life, and is supplemented with relevant examples of questions. The appearance of an attractive electronic module is also considered important by students. In the context of an independent curriculum, students experience difficulties in learning renewable energy material, with several factors causing difficulties such as material that is difficult to understand, too many formulas, limited learning resources, and lack of application of examples and various learning orientations. This research shows the need to develop electronic modules that are complete, interactive, and in accordance with the needs of students to increase their understanding and interest in learning Physics